Performance evaluation of human identification based on ECG signal - Amiruddin, Ainunjariah; Khalifa, Othman Omran; Rabih, Fadlallah Ali Fadlallah (Institute of Electrical and Electronics Engineers Inc., 2015)
This Biometric identification technology has been growing over the last years with increasing demand to improve the technology and provide a better security for the society. In this paper, a biometric identification system using electrocardiogram (ECG) has been introduced and to compete with the existing biometric identification systems such as fingerprint, signature, voice and face. Various studies have been conducted by previous researchers in order to find the best procedures and techniques to provide an ECG identification system with the lowest percentage of error. A proposed scheme is presented in this work based on the previous studies. It is illustrate the uniqueness of ECG signal for each person thus it can be used to identify an individual